2008
DOI: 10.4049/jimmunol.181.8.5306
|View full text |Cite
|
Sign up to set email alerts
|

Human Memory B Lymphocyte Subsets Fulfill Distinct Roles in the Anti-Polysaccharide and Anti-Protein Immune Response

Abstract: There is controversy on the role of IgM memory and switched memory B lymphocytes in the Ab response to T cell-independent and T cell-dependent Ags. We transplanted SCID/SCID mice with human B lymphocyte subsets and immunized them with heat-inactivated Streptococcus pneumoniae or with a pneumococcal vaccine. Inactivated S. pneumoniae and soluble pneumococcal capsular polysaccharides elicited an IgM anti-polysaccharide and anti-protein Ab response from IgM memory B lymphocytes and an IgG anti-polysaccharide and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 37 publications
2
44
0
Order By: Relevance
“…In contrast, we provide evidence that early changes in the phenotype of circulating B cells in alemtuzumab-treated patients correlated with the development of DSA posttransplantation. A previous report in patients with multiple sclerosis showed that even multiple doses of alemtuzumab failed to significantly decrease CD27 + memory B cell percentages 1 mo after administration (32) Abs against pneumococcal surface protein A, a T cell-dependent Ag (33). Similarly, the CD27 + B cell subset isolated from the peripheral blood of sensitized patients was able to produce alloantibodies in vitro (34).…”
Section: Discussionmentioning
confidence: 92%
“…In contrast, we provide evidence that early changes in the phenotype of circulating B cells in alemtuzumab-treated patients correlated with the development of DSA posttransplantation. A previous report in patients with multiple sclerosis showed that even multiple doses of alemtuzumab failed to significantly decrease CD27 + memory B cell percentages 1 mo after administration (32) Abs against pneumococcal surface protein A, a T cell-dependent Ag (33). Similarly, the CD27 + B cell subset isolated from the peripheral blood of sensitized patients was able to produce alloantibodies in vitro (34).…”
Section: Discussionmentioning
confidence: 92%
“…However, various studies have shown that PPS induce efficient activation of IgM + memory B cells (IgM + IgD + CD27 + ) and generation of long-lived plasma cells (CD38 + CD20 low ). This is accompanied by the generation and persistence of IgM and IgG antibodies against PPS [101][102][103][104][105][106][107][108]. IgM + memory B cells circulating in the blood are the peripheral correlates of the marginal zone B cells of the spleen.…”
Section: Immunogenicitymentioning
confidence: 99%
“…Adoptive transfer of human lymphocytes was performed as previously reported (46). Four buffy coats were provided by the Blood Bank of Stanford University.…”
Section: Isolation Of B Cells By Rosette Formation and Purification Omentioning
confidence: 99%